3D printed microfluidic device for mechanical lysis - Valappai Mohamed Farook Shariba Beevi (2017)
The purpose of this project is to produce a microfluidic device for mechanical cell lysis. Microfluidic device consist of group of channels connected together from inlet to outlet. Over the years, the microfluidic device is becoming popular in almost every field, because only a small portion of reagents (in a range of microliter) is required to get the instantaneous result. The conventional method for fabrication of microfluidic device was mostly done by soft lithography, which consists of numerous steps. It takes almost a week to get a fully fabricated device, which is extremely time-consuming. 3D printing technology could solve this issue as it provides fast and easy construction of the device. With the suitable 3D printer for fabricating microfluidic device, it can be printed instantaneously. For that, the design of microfluidic device was drawn using the Computer Aided Design (CAD) software, Solidworks. The device was then 3D printed by Stereolithography (SLA) printer, form2 with clear resin. Printing the device for the first time wasn’t successful, as the channel wasn’t printed. With few changes made, the device was printed again and testing of fluid flow on the channel was conducted. There was a leakage from the part. Thus, the accuracy of the printed part was examined under stereomicroscope. According to obtained tolerance in x, y and z direction and the testing of fluid flow, the device was redesigned. From there, the experiment was conducted using micro-beads and color dye. Although 3Dprinting a microfluidic device shorten the time of fabrication, receiving a part with 100 percent accuracy is very challenging, especially with minute dimension and more optimization is required. The actual dimension of the part is usually varies from the designed dimension. Thus, when designing a 3D model, considering the shrinkage value and tolerance helps to achieve almost close to the preferred dimension. Moreover, the resolution of the printer is important. The resolution doesn’t mean the smallest hole or gap has to be followed in the design.